Boosting Performance: Peran Budaya, Lingkungan, dan Pengalaman di PT PLN ULP Kersik Tua - Wahyu Juari Setiawan; Budi Darma; Rezki Agrisa Ditama; Muhammad Munawir Pohan (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2025)
This study aims to analyze the influence of organizational culture, work environment, and work experience on employee performance. The approach used is quantitative with associative research type. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression. Prior to hypothesis testing, instrument testing (validity and reliability) and classical assumption tests were conducted including normality, multicollinearity, and heteroscedasticity, which indicated that the data were worthy of further analysis. The results of the study indicate that organizational culture, work environment, and work experience simultaneously have a significant effect on employee performance with a strong contribution level. Partially, only organizational culture was proven to have a significant effect on performance, while work environment and work experience did not show a significant effect individually. These findings indicate that organizational culture has a dominant role in driving improved employee performance. Companies are advised to strengthen the internalization of organizational cultural values ​​as a primary strategy in improving performance. This study also provides an empirical contribution to the study of organizational behavior, particularly in the context of BUMN in the energy sector.